Sintesis Biodiesel Dari Minyak Jelantah Dalam Reaktor Ultrasonik - Priscilla, Tiara; Irwan, Muh.; Arifin, Zainal (Jurnal Energi Baru dan Terbarukan, 2024)
Waste cooking oil is considered promising alternative to biodiesel production as substitute for diesel fuel becauce it it is environmentally friendly, biodegradable, non-toxic, and renewable energy source. This study aims to obtain the optimum operating conditions of ultrasonic reactors in biodiesel production using Response Surface Methodology (RSM) method. RSM with CCD was used to determine effect of transducer distance (1-5 cm) and reaction time (5-20 minutes) on biodiesel yield, to determine optimal operating conditions and to optimize biodiesel yield. In this study, waste cooking oil was transesterified into biodiesel with ultrasonic waves to intensify reaction. Transesterification waste cooking oil was carried out in a sodium hydroxide catalyst using methanol. Solution inserted into the erlenmeyer with the transducer distance and reaction time to determined by RSM. Once the reaction time was reached, mixture of biodiesel and glycerol was separated in separate funnel. Biodiesel obtained was then washed and evaporated the remaining solvent. Biodiesel yield was obtained under 88.33% under optimal conditions of 1 cm transducer distance with reaction time 20 minutes. Reaction time was the most important parameter based on the ANOVA test. The properties biodiesel produced including kinematic viscosity, density, acid number, methyl ester contents and monoglicerida have met the requirements of standards SNI 7182: 2015.